Associations of caesarean delivery and the occurrence of neurodevelopmental disorders, asthma or obesity in childhood based on Taiwan birth cohort study. Issue 9 (27th September 2017) - Chen, Ginden; Chiang, Wan-Lin; Shu, Bih-Ching; Guo, Yue Leon; Chiou, Shu-Ti; Chiang, Tung-liang
Abstract : Objectives: Whether birth by caesarean section (CS) increases the occurrence of neurodevelopmental disorders, asthma or obesity in childhood is controversial. We tried to demonstrate the association between children born by CS and the occurrence of the above three diseases at the age of 5.5 years. Methods: The database of the Taiwan Birth Cohort Study which was designed to assess the developmental trajectories of 24 200 children born in 2005 was used in this study. Associations between children born by CS and these three diseases were evaluated before and after controlling for gestational age (GA) at birth, children's characteristics and disease-related predisposing factors. Results: Children born by CS had significant increases in neurodevelopmental disorders (20%), asthma (14%) and obesity (18%) compared with children born by vaginal delivery. The association between neurodevelopmental disorders and CS was attenuated after controlling for GA at birth (OR 1.15; 95% CI 0.98 to 1.34). Occurrence of neurodevelopmental disorders steadily declined with increasing GA up to ≤40–42 weeks. CS and childhood asthma were not significantly associated after controlling for parental history of asthma and GA at birth. Obesity in childhood remained significantly associated with CS (OR 1.13; 95% CI 1.04 to 1.24) after controlling for GA and disease-related factors. Conclusions: Our results implied that the association between CS birth and children's neurodevelopmental disorders was significantly influenced by GA. CS birth was weakly associated with childhood asthma since parental asthma and preterm births are stronger predisposing factors. The association between CS birth and childhood obesity was robust after controlling for disease-related factors.